2023
DOI: 10.1126/sciadv.ade2693
|View full text |Cite
|
Sign up to set email alerts
|

A secreted sirtuin from Campylobacter jejuni contributes to neutrophil activation and intestinal inflammation during infection

Sean M. Callahan,
Trevor J. Hancock,
Ryan S. Doster
et al.

Abstract: Histone modifications control numerous processes in eukaryotes, including inflammation. Some bacterial pathogens alter the activity or expression of host-derived factors, including sirtuins, to modify histones and induce responses that promote infection. In this study, we identified a deacetylase encoded by Campylobacter jejuni which has sirtuin activities and contributes to activation of human neutrophils by the pathogen. This sirtuin is secreted from the bacterium into neutrophils, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 102 publications
0
4
0
Order By: Relevance
“…In addition, recent studies have found that Synergistes appears to be more prevalent in people with tooth and gum disease than in healthy people [42,43]. Both Clostridium and Campylobacter are associated with digestive tract disorders, with the former releasing an endotoxin causing mucosal necrosis [44,45] and the latter causing enteritis [46]. The increased abundance of these genera also suggests that inflammation may be present in the rumens of cows with indigestion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have found that Synergistes appears to be more prevalent in people with tooth and gum disease than in healthy people [42,43]. Both Clostridium and Campylobacter are associated with digestive tract disorders, with the former releasing an endotoxin causing mucosal necrosis [44,45] and the latter causing enteritis [46]. The increased abundance of these genera also suggests that inflammation may be present in the rumens of cows with indigestion.…”
Section: Discussionmentioning
confidence: 99%
“…This sirtuin is secreted into neutrophils, where it binds to and deacetylates the host's histones, thereby fostering neutrophil activation and the generation of neutrophil extracellular traps (NETs). These NETs have been observed to concentrate within abscess formations in colonic crypts, suggesting a targeted immune response by neutrophils to C. jejuni within the intestinal environment [73]. These processes are instrumental in driving the inflammation and pathology observed in campylobacteriosis.…”
Section: Diarrhea To Disorder: Tracing the Path From Campylobacter Je...mentioning
confidence: 99%
“…These processes are instrumental in driving the inflammation and pathology observed in campylobacteriosis. Interestingly, SliP's translocation into neutrophils is facilitated by the bacterium's flagella, suggesting a sophisticated mechanism of host interaction [73]. Upon secretion, SliP's association with neutrophil histones leads to diminished acetylation, directly influencing the host's epigenetic landscape.…”
Section: Diarrhea To Disorder: Tracing the Path From Campylobacter Je...mentioning
confidence: 99%
See 1 more Smart Citation